2022
DOI: 10.1055/s-0042-1750178
|View full text |Cite
|
Sign up to set email alerts
|

International Multicenter Study of Clinical Outcomes of Sinonasal Melanoma Shows Survival Benefit for Patients Treated with Immune Checkpoint Inhibitors and Potential Improvements to the Current TNM Staging System

Abstract: Objectives Sinonasal mucosal melanoma (SNMM) is an extremely rare and challenging sinonasal malignancy with a poor prognosis. Standard treatment involves complete surgical resection, but the role of adjuvant therapy remains unclear. Crucially, our understanding of its clinical presentation, course, and optimal treatment remains limited, and few advancements in improving its management have been made in the recent past. Methods We conducted an international multicenter retrospective analysis of 505 SN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
(40 reference statements)
1
15
0
3
Order By: Relevance
“…Genetic analysis also allows for the identification of molecular targets for modern targeted therapies. Several studies on tumor-infiltrating lymphocytes and aspects of the PD-L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and we strongly encourage research into the clinical response to treatment with immune checkpoint inhibitors in sinonasal cancers such as recently reported on MMM [ 17 ]. Next-generation sequencing identified recurrent subtype-unique mutations including: APC , CTNNB1 , PIK3CA and KRAS in ITAC, EGFR and CDKN2A in SNSCC, NRAS and NF1 in MMM, IDH2 in SNUC, and ARID1A , SMARCB1 and SMARCA4 in SNEC, SNUC and TCS [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…Genetic analysis also allows for the identification of molecular targets for modern targeted therapies. Several studies on tumor-infiltrating lymphocytes and aspects of the PD-L1/PD1 checkpoint have indicated a role for immunotherapy in several sinonasal tumor subtypes [ 10 , 11 , 12 , 13 , 14 , 15 , 16 ], and we strongly encourage research into the clinical response to treatment with immune checkpoint inhibitors in sinonasal cancers such as recently reported on MMM [ 17 ]. Next-generation sequencing identified recurrent subtype-unique mutations including: APC , CTNNB1 , PIK3CA and KRAS in ITAC, EGFR and CDKN2A in SNSCC, NRAS and NF1 in MMM, IDH2 in SNUC, and ARID1A , SMARCB1 and SMARCA4 in SNEC, SNUC and TCS [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
mentioning
confidence: 87%
“…The high incidence of recurrences and distant failures in MMM is the main cause of death, with reported one-, three-, and five-year recurrence-free and overall survival of 61, 31, and 22%, and 78, 49, and 38%, respectively [ 17 ]. With the aim to tackle this, Freiberger et al presented a pioneer longitudinal study on MMM describing an observed ‘switch’ from KRAS , KIT or no mutation in primary tumors to solely genomic alterations in NRAS in recurrent tumor, after developing resistance to immunotherapy.…”
mentioning
confidence: 99%
“…Ein isolierter Septumtumor scheint mit einer guten Prognose verbunden zu sein [5]. Faktoren, welche die Prognose der Erkrankung negativ beeinflussen, sind ein fortgeschrittenes Lebensalter zum Zeitpunkt der Diagnose sowie eine Tumorgröße von mehr als 3-4 cm [6,7].…”
Section: Abkür Zungenunclassified
“…Die adjuvante Strahlentherapie ist ein fester Bestandteil der Behandlung von SNSM, insbesondere in der R1-oder RX-Situation. Eine Strahlentherapie scheint die lokoregionäre Kontrolle [13] sowie das Überleben zu verbessern [7], wobei die Datenlage hierzu nicht eindeutig ist [14,15]. Der Literatur zufolge liegt das Risiko eines Lokalrezidivs beim SNSM nach chirurgischer Therapie mit adjuvanter Radiatio bei bis zu 50 % [15].…”
Section: Strahlentherapieunclassified
See 1 more Smart Citation